2014
DOI: 10.1016/j.intell.2014.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognitive versus emotional intelligence in Iowa Gambling Task performance: What's emotion got to do with it?

Abstract: Debate persists regarding the relative role of cognitive versus emotional processes in driving successful performance on the widely used Iowa Gambling Task (IGT). From the time of its initial development, patterns of IGT performance were commonly interpreted as primarily reflecting implicit, emotion-based processes. Surprisingly, little research has tried to directly compare the extent to which measures tapping relevant cognitive versus emotional competencies predict IGT performance in the same study. The curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
47
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 28 publications
11
47
1
6
Order By: Relevance
“…This would be consistent with observations of unimpaired neurocognitive performance in PB-samples of previous studies (Black et al, 2012;Voth et al, 2014). Furthermore, within the current study, we revealed some correlations between decision-making performance and the neuropsychological tasks as well as intelligence, which were partly consistent with previous studies (Brand et al, 2008;Gansler et al, 2011;Schiebener et al, 2011;Webb et al, 2014). However, the validity of the correlations is limited due to small sample sizes.…”
Section: Discussionsupporting
confidence: 93%
“…This would be consistent with observations of unimpaired neurocognitive performance in PB-samples of previous studies (Black et al, 2012;Voth et al, 2014). Furthermore, within the current study, we revealed some correlations between decision-making performance and the neuropsychological tasks as well as intelligence, which were partly consistent with previous studies (Brand et al, 2008;Gansler et al, 2011;Schiebener et al, 2011;Webb et al, 2014). However, the validity of the correlations is limited due to small sample sizes.…”
Section: Discussionsupporting
confidence: 93%
“…As part of a larger study, participants completed several measures of EI, AS, and psychopathology. Prior data from a larger study that included other outcomes from this sample have been reported elsewhere (Killgore, Weber, Schwab, Deldonno, Kipman, Weiner et al, 2012;Killgore, Schwab, Tkachenko, Webb, DelDonno, Kipman et al, 2013;Webb et al, 2013;Webb, DelDonno, & Killgore, 2014), whereas the findings of the mediation analyses and AS indices reported herein are novel and have not been previously published. This research protocol was reviewed and approved by the McLean Hospital Institutional Review Board and the U.S. Army Human Research Protection Office.…”
Section: Participantsmentioning
confidence: 89%
“…ASI: Anxiety Sensitivity Intex; MSCEIT: Meyer Salovey Caruso Emotional Intelligence Test; EQ-i: Bar-On Emotional Quotient Inventory; SREIS: Self-Rated Emotional Intelligence Scale; PAI ANX: Anxiety Scale of the Personality Assessment Inventory. A subset of the correlations listed above for the emotional intelligence measures have been published previously inWebb, DelDonno, and Killgore (2014), but are presented here along with the anxiety measures for completeness. *p < .05. yp < .001.…”
mentioning
confidence: 99%
“…At least intuitively, decision‐making and intelligence should be inter‐related. However, empirical studies in cognitive psychology, which typically infer decision‐making by performance in gambling tasks, have shown that this relationship is complex in both adults (Toplak, Sorge, Benoit, West, & Stanovich, ; Webb, DelDonno, & Killgore, ) and children (Crone & van der Molen, ; Lehto & Elorinne, ; Li et al ., ; Smith, Xiao, & Bechara, ). With adults, studies tend to show relationships in clinical populations – perhaps reflecting the presence of multiple deficits in their functioning (Toplak et al ., ) – and only an asymmetric dependence in the general population, such that general cognitive ability is not dependent on the intactness of decision‐making, but decision‐making is influenced by the intactness of cognitive ability.…”
Section: Introductionmentioning
confidence: 99%
“…With this task, therefore it is difficult to distinguish risk‐taking from contingency learning. Despite this, some research using the IGT has shown that successful performance is driven by cognitive rather than by more implicit, emotion‐based processes in both adults (Webb et al ., ) and children (Li et al ., ). That is, although performance on the IGT is typically interpreted as reflecting ‘hot’ (affective) decision‐making, it appears that it is also linked with deliberate, cognitive capacities (associated with intelligence).…”
Section: Introductionmentioning
confidence: 99%